2010
DOI: 10.1051/0004-6361/201015274
|View full text |Cite
|
Sign up to set email alerts
|

Phase connecting multi-epoch radio data for the ultracool dwarf TVLM 513-46546

Abstract: Context. Radio data obtained for the ultracool dwarf TVLM 513-46546 has indicated a rotation period of ≈1.96 h via regular radio pulses, but how stable is this period. This has major implications regarding the stability of the magnetic field structures responsible for the radio emission from the ultracool dwarf. Aims. The aim of the present work is to investigate the stability of this rotation period using two datasets taken ≈40 days apart, some 12 months after the first report of periodical pulses in the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…Wolszczan & Route (2014) reported stable optical and radio emission for 7 and 5 years respectively, that produce the same period with precision up to ∼20ms. Berger et al (2008), Doyle et al (2010) and Wolszczan & Route (2014) report a correlation between the Hα peaks and radio flares with approximately 0.4 phase offset, suggesting that the optical and radio variability originates from a large-scale dipolar magnetic field that is stable for at least a decade. Wolszczan & Route (2014) also reported that the period between bursts may be gradually shortening, possibly due to migration of spots towards the equator and differential rotation.…”
Section: Tvlm 513-46546mentioning
confidence: 95%
See 1 more Smart Citation
“…Wolszczan & Route (2014) reported stable optical and radio emission for 7 and 5 years respectively, that produce the same period with precision up to ∼20ms. Berger et al (2008), Doyle et al (2010) and Wolszczan & Route (2014) report a correlation between the Hα peaks and radio flares with approximately 0.4 phase offset, suggesting that the optical and radio variability originates from a large-scale dipolar magnetic field that is stable for at least a decade. Wolszczan & Route (2014) also reported that the period between bursts may be gradually shortening, possibly due to migration of spots towards the equator and differential rotation.…”
Section: Tvlm 513-46546mentioning
confidence: 95%
“…Highly polarised radio bursts were reported by Hallinan et al (2007); Berger et al (2008) and Doyle et al (2010). Doyle et al (2010) showed the data contained a series of consecutive periodic bursts with stable shape of the light curve, but changing shape/structure of the bursts. Wolszczan & Route (2014) reported stable optical and radio emission for 7 and 5 years respectively, that produce the same period with precision up to ∼20ms.…”
Section: Tvlm 513-46546mentioning
confidence: 99%
“…Detected bursts were highly circularly polarized and lasted multiple minutes. Both the persistent and burst emission features were later confirmed by Osten et al (2006), Hallinan et al (2006), Hallinan et al (2007), Berger et al (2008), Forbrich &Doyle et al (2010) through observations at 8.5 GHz and 4.9 GHz. Further, Hallinan et al (2007) and Lane et al (2007, optical) detected a pulse periodicity of ∼2 hr, consistent with the stellar rotation rate.…”
Section: Target Historymentioning
confidence: 70%
“…Figure 6 shows the comparison of our simulation with observations (see Hallinan et al 2010, for further details). The observation is taken from 2008 May 19 (UT) at 4725 MHz for the M8.5V dwarf TVLM 513.…”
Section: Comparison With Observationsmentioning
confidence: 99%